2012, No. 12, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting theory and practice Greta Vetriakaitė, Kristina Rudžionienė, Evaluation of USA GAAP and EU accounting harmonization, 7 Jūratė Klusavičiūtė, Kristina Rudžionienė, Determinants of liabilities‘ disclosure in financial statements of Lithuanian listed companies, 19 Renata Smirnova, Kristina Rudžionienė, Factors of the corporate social responsibility disclosure in financial statements, 31 Rasa Subačienė, Džemilė Jakubauskaitė, Aspects of financial and tax accounting of tangible fixed assets, 41 Financial analysis and measurement, Gerda Venckevičiūtė, Gražina Jatulevičienė, Economy, efficiency, effectiveness and efficacy (four Es‘) concept in performance measurement, 49 Lukas Giriūnas, Internal control and its place in a company‘s management structure, 58 Jovita Pliustienė, Strategic planning for tourism and rural tourism sector development opportunities, 67 Neringa Slavinskaitė, Complex evaluation of operating activity efficiency of dairy industry companies, 82 Jokūbas Leipus, Jonas Mackevičius, The stability of Islamic Banks throughout the global financial crisis, 95 Liuda Villis, The essence and models of the supervision of major financial institutions, 105